2019
DOI: 10.3390/ma12050802
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect of Graphene Oxide with Low Oxygen Content on Portland Cement Based Composites

Abstract: The current study presents research into the effect of graphene oxide (GO) with a carbon to oxygen ratio of 4:1 on the fluidity, hydration, microstructure, mechanical and physical properties of Portland cement pastes and mortars. The amounts of GO investigated were 0.02%, 0.04%, and 0.06% by weight of cement, while for mortars, an extra composition with 0.1% was also prepared. According to the results, the fluidity of cement paste and mortar increased and the hydration process was slightly retarded with the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 52 publications
1
6
0
3
Order By: Relevance
“…The peak intensity of the portlandite lowered as time passed. These results are consistent with previous findings in the literature [ 23 , 28 , 49 ].…”
Section: Resultssupporting
confidence: 94%
“…The peak intensity of the portlandite lowered as time passed. These results are consistent with previous findings in the literature [ 23 , 28 , 49 ].…”
Section: Resultssupporting
confidence: 94%
“…Quando foi adicionado 0,10% de GOv à pasta de cimento, observou-se um aumento de 14,7% na resistência mecânica. Esse valor é similar ao descrito por KUDŽMA e colaboradores, que observaram o aumento de cerca de 15% ao adicionar a mesma quantidade de GO [35]. A série de ensaios mostrou um pico de resistência à compressão, quando foi adicionado 0,30% de GOv à pasta de cimento, com incremento de 65,6% na resistência à compressão em relação ao material de referência.…”
Section: Figuraunclassified
“…BABAK e colaboradores [5], em pesquisas realizadas com GO e cimento, observaram que os produtos de silicatos de cálcio hidratado do cimento se depositaram na superfície GO, que atuou como um local de nucleação e os silicatos apresentaram uma grande adesão em sua superfície. KUDŽMA e colaboradores [35] observaram que a melhora nas propriedades mecânicas pode estar associada, principalmente, à compactação da estrutura, redução na descontinuidade e na porosidade da microestrutura da matriz cimentícia. Já WANG e colaboradores [20] observaram que dosagens de GO resultam em cristais de portlandita mais refinados.…”
Section: Figuraunclassified
See 1 more Smart Citation
“…Due to the excellent mechanical properties of GO, the possibility of its application in cement has been extensively explored. Previous studies have reported that addition of GO promoted the hydration of cement and significantly increased the compressive and flexural strength of cement [37,38,39]. In a recent study, Lv et al [40] found that the addition of GO was capable of affecting the shape of cement hydration products, such as ettringite (AFt) and monosulfate (AFm).…”
Section: Introductionmentioning
confidence: 99%